2018
DOI: 10.1186/s12913-018-3248-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the performance of mental health, drug and alcohol comorbidities based on ICD-10-AM and medical records for predicting 12-month outcomes in trauma patients

Abstract: BackgroundMany outcome studies capture the presence of mental health, drug and alcohol comorbidities from administrative datasets and medical records. How these sources compare as predictors of patient outcomes has not been determined. The purpose of the present study was to compare mental health, drug and alcohol comorbidities based on ICD-10-AM coding and medical record documentation for predicting longer-term outcomes in injured patients.MethodsA random sample of patients (n = 500) captured by the Victorian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Demographic, injury event, injury severity, level of definitive care in the trauma system, and in-hospital outcome data were extracted from the registries to enable a comparison of cases opting for email or telephone completion. The International Classification of Diseases, Tenth Revision, Australian Modification diagnosis codes were mapped to the Charlson Comorbidity Index and indicators for preexisting mental health, drug, and alcohol conditions 19,20 . The patient’s residential postcode was used to map to quintiles of the Index of Relative Socioeconomic Advantage and Disadvantage to provide a measure of socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic, injury event, injury severity, level of definitive care in the trauma system, and in-hospital outcome data were extracted from the registries to enable a comparison of cases opting for email or telephone completion. The International Classification of Diseases, Tenth Revision, Australian Modification diagnosis codes were mapped to the Charlson Comorbidity Index and indicators for preexisting mental health, drug, and alcohol conditions 19,20 . The patient’s residential postcode was used to map to quintiles of the Index of Relative Socioeconomic Advantage and Disadvantage to provide a measure of socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
“…The International Classification of Diseases, Tenth Revision, Australian Modification diagnosis codes were mapped to the Charlson Comorbidity Index and indicators for preexisting mental health, drug, and alcohol conditions. 19,20 The patient's residential postcode was used to map to quintiles of the Index of Relative Socioeconomic Advantage and Disadvantage to provide a measure of socioeconomic status. The Index of Relative Socioeconomic Advantage and Disadvantage uses information about the economic and social conditions of households and people in an area to provide a summary measure of socioeconomic advantage and disadvantage.…”
Section: Data Extractmentioning
confidence: 99%
“…The pooled estimate of effect size was 0.52 (95% CI 0.43,0.6) (I 2 = 98.9%); i.e., 52% of the participants returned to some form of employment. There were 14 studies (45,47,48,50,53,(55)(56)(57)(58)(59)(60)(61)(62)(63) that reported on RTW up to 12 months, one of which had reported on two groups of trauma patients. The pooled estimate of effect size was 0.64 (95% CI 0.53,0.5) (I 2 = 99.2%); i.e., 64% of the participants returned to some form of employment.…”
Section: Return-to-work (Rtw) 1a Back To Any Work (Yes or No)mentioning
confidence: 99%
“…4B(i). EQ-5D Index Five studies (53,56,68,78,79) provided relevant data for calculation of a summarized estimate of effect size for EQ-5D Index. Of these, two studies (53,79) measured the QOL at different time points, while one study (78) included two groups of trauma patients.…”
Section: B Eq-5dmentioning
confidence: 99%
“…Some studies have found the prevalence of comorbidities to be lower in administrative data than in medical chart review, 30,31 whereas others have reported that there was no notable difference. 32,33 One of the latter studies was based on a population with acute trauma in Victoria, in which an institution-specific administrative data set, which captures details similar to those in the Victorian Admitted Episodes Dataset and much more, was compared with medical records. Therefore, we consider that using administrative admissions data rather than chart reviews in our Victorian study most likely had no significant influence on the findings while offering a great practical advantage.…”
Section: Limitationsmentioning
confidence: 99%